2020
DOI: 10.1055/s-0040-1705106
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of an Electronic Medical Record Tool for Childhood Obesity by Primary Care Providers

Abstract: Background Primary care providers are tasked with the increasingly difficult job of addressing childhood obesity during clinic visits. Electronic medical record (EMR)-enabled decision-support tools may aid providers in this task; however, information is needed regarding whether providers perceive such tools to be useful for addressing nutrition and physical activity lifestyle behaviors. Objectives This study aimed to evaluate the usefulness and usability of FitTastic, an EMR-enabled tool to support p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 24 publications
0
32
0
Order By: Relevance
“…Several studies have demonstrated the explanatory power of perceived usefulness and perceived ease of use in interpreting the specific behaviors of GPs, such as adherence to guidelines, the use of health information technology, etc. [ 38 , 39 , 40 , 41 ]. The results of the analysis of the use of telehealth services showed that the main factors influencing the use of telemedicine services, in addition to perceived usefulness and ease of use, were the following variables: social impact, favorable conditions, and trust [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated the explanatory power of perceived usefulness and perceived ease of use in interpreting the specific behaviors of GPs, such as adherence to guidelines, the use of health information technology, etc. [ 38 , 39 , 40 , 41 ]. The results of the analysis of the use of telehealth services showed that the main factors influencing the use of telemedicine services, in addition to perceived usefulness and ease of use, were the following variables: social impact, favorable conditions, and trust [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of TAM, several studies have demonstrated the explanatory power of these two factors in interpreting specific behaviors of health professionals, such as adherence to guidelines, the use of health information technology, etc. [ 38 , 39 , 40 , 41 ].…”
Section: Theoretical Basicsmentioning
confidence: 99%
“…On the other hand, 1 benefit of FitTastic that providers identified previously was that use of FitTastic with all families (not just children with obesity) may reduce the stigma associated with completing FitTastic behavioral assessments. 20 Providers at the intervention clinics chose to continue FitTastic after the completion of the study, currently up to 5-years after initiation, speaking to those providers' favorable views of FitTastic.…”
Section: Discussionmentioning
confidence: 99%
“… 12 Using EHR templates and integrated tools such as an automated body mass index (BMI) calculator improves obesity diagnosis precision. 2 , 3 , 4 , 5 , 6 , 18 , 19 , 20 It is important to update tools that are so vital to clinical practice. 2 …”
Section: Introductionmentioning
confidence: 99%